Monolithic Carbon Nanotube Film Thermoelectric Generator - Hasan, Mohammed Nazibul; Muthalif, Asan G. A.; Saleh, Tanveer; Zhang, Zhi-Bin; Mohamed Ali, Mohamed Sultan (IEEE Xplore, 2024)
The design and development of a thermoelectric generator (TEG) with minimal internal resistance is crucial for achieving high output power in self-powered wearable technologies. This work presents a novel flexible TEG comprising single-walled carbon nanotube (SWCNT) thermoelements, fabricated through a sacrificial molding process. Different from the traditional TEG structural design, our TEG’s p- and n-type SWCNT thermoelements are formed monolithically without any interconnections. This integration eliminates the presence of internal resistance within the device. Equipped with eight pairs of the p- and n-type SWCNT thermoelements, the TEG exhibits an open-circuit voltage (Voc) of ∼21.82 mV and an internal resistance of ∼16.56 , corresponding to a maximum output power of approximately 7.19 μW at a temperature gradient (1T ) of 50 ◦C. Additionally, the TEG demonstrated its capability to harvest energy from a fingertip, generating a Voc of around 2.58 mV at a 1T of 8.8 ◦C. These results highlight the potential of the monolithically formed SWCNT thermoelements for achieving high-power density TEGs.